2022
DOI: 10.3390/foods11030448
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential of Cookies Formulated with Date Seed Powder

Abstract: Utilising major waste products from the food industry can have both a great environmental impact and be a means to improve consumer health. Date seed is a food industry byproduct that has been proven to have high nutritional value. The aim of this work was to measure the total polyphenolic content (TPC), flavonoids, and antioxidant activity of the seeds of six date fruit varieties, Fard, Khalas, Khinaizi, Sukkary, Shaham, and Zahidi, and to use those seeds to enhance the antioxidant value of cookies by partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…The decreasing trend of “ a *” values can be credited to factors like temperature, sugar, water availability, and Maillard reaction during baking, leading to darker red hues . The findings are from previous studies reporting alterations in biscuit color due to incorporating pulp or seed powders . Color deterioration in storage is an important factor in the commercial viability of the product.…”
Section: Resultsmentioning
confidence: 81%
“…The decreasing trend of “ a *” values can be credited to factors like temperature, sugar, water availability, and Maillard reaction during baking, leading to darker red hues . The findings are from previous studies reporting alterations in biscuit color due to incorporating pulp or seed powders . Color deterioration in storage is an important factor in the commercial viability of the product.…”
Section: Resultsmentioning
confidence: 81%
“…Apart from the cultivar associated differences, interlaboratory variations of polyphenolic content may also be attributed to differences in extraction protocols. Najjar et al (2022) reported variations in TPC of Khalas cultivar (range from 0.39 to 0.82 mg GAE g −1 DW) when extracted in water under different sample: solvent ratio levels. Such heterogenicity was also identified in this review wherein the anthocyanin content of 50% aqueous acetone extract from Deglet Nour was reported to be 20 times higher by Metoui et al (2019) than the TAC content reported by Smaoui et al (2020) using similar extraction solvents.…”
Section: Resultsmentioning
confidence: 99%
“…The biscuits were formulated with a 25/75 mix of red/yellow date powder and were the most overall liked. Najjar et al [ 106 ] studied the substitution of wheat flour for ground date seed (2.5, 5.0, and 7.5%) in a cookie’s formulation to enhance its antioxidant capacity. The results showed that cookies with date seed powder contained significant amounts of TPC and flavonoids, leading to an increase in the antioxidant capacity in comparison with the control cookies without date seed powder.…”
Section: Application Of Date Fruits Products and Co-products In Foodsmentioning
confidence: 99%